Cyberstalking Crime in The Perspective of Islamic Criminal Law - Inaya, Ardina Nur; Yazid, Imam (JURNAL MERCATORIA, 2025)
This article aims to analyze the adequacy of cyberstalking regulation within Indonesian criminal law and to examine it from the perspective of Islamic criminal law. The study focuses on the absence of a specific cyberstalking offense in Indonesian criminal legislation and on how Islamic law positions such conduct within the framework of jarimah ta‘zīr. The research employs a normative juridical method using statutory, conceptual, and comparative approaches. The findings indicate that Indonesian criminal law still relies on the provisions of the Criminal Code (KUHP), the Electronic Information and Transactions Law (UU ITE), and the Sexual Violence Crime Law (UU TPKS), all of which do not fully capture the digital, repetitive, and multidimensional nature of cyberstalking. From the perspective of Islamic criminal law, cyberstalking is classified as a jarimah ta‘zīr because it violates the principles of ḥifẓ al-nafs and ḥifẓ al-ʿird, thereby leaving the determination of sanctions to judicial ijtihād based on public interest. This study underscores the urgency of regulatory reform to formulate a clearer and more integrative cyberstalking offense that aligns with victim protection principles in accordance with maqāṣid al-sharīʿah.